Dendritic architectures with positively charged cores and negatively charged shells - Schunk, Torsten; Hirsch, Andreas (European Journal of Organic Chemistry, 2012)
A new family of dipolar ionic dendrimers that consist of a cationic pyridinium core surrounded by a negatively charged shell of carboxylic acids was successfully synthesized and characterized. Both spherical architectures and examples of amphiphiles with a dipolar head group were synthesized. Studies of the aggregation behaviour in aqueous solution by determining the cmc values were performed. This new type of dipolar core-shell dendrons can be considered as molecular architectures that contain a positively charged nucleus covalently incorporated within a negatively charged shell. Dipolar ionic dendrimers that consist of dendronized pyridinium units surrounded by a shell of carboxylic acids are a new family of dendritic architectures in which opposite charges are organized within specific areas of one macromolecule. They can be considered as molecular architectures that contain a positively charged nucleus covalently incorporated within a negatively charged shell. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.